Narrating communities: constructing and challenging Mennonite Canadian identities through narrative - Michael, Julia; Justus Liebig University Giessen (My University, 2017)
Contemporary life is complex and wrought with challenges. To be able to make sense of the multiple information people are confronted with and to create meaning we tell stories. By connecting information and bringing together events in a cohesive and coherent fashion and in an aesthetic form, we make new meanings, establish relationships, and provide memories for further generations. Yet, naturally, these stories do not portray reality as it presents itself to individuals. Rather, they portray a construction of realities, held together by means of storytelling. As a result, stories do not only function as means of structuring experience, but they also create new meanings and therefore have an effect on the world they are presenting (cf. Neumann and A. Nünning 2008). Stories are vehicles to make sense of the world, while simultaneously having an effect on it, or, as Robert Kroetsch phrased it, [i]n a sense, we haven t got an identity until somebody tells our story. The fiction makes us real (Kroetsch, Bacque, and Gravel 1970: 63).To explore this phenomenon this thesis focuses on Mennonite identities and storytelling, the intricate relationship between narratives and the construction of cultural identities, and the formation of communities around cultural memories. Mennonite identities have traditionally been characterized by religion, ethnicity, or history. While all of these markers are important, a predominant focus on them has established binary identities: people are either clearly Mennonite because they identify with the history and faith and have a long line of Mennonite ancestors, or they do not and are therefore not Mennonite. Yet, faced with contemporarychallenges in the Canadian context, such as the deconstruction of settlement history, the exploration of the colonial history, and debates on feminism and sexualities that have entered Mennonite congregations all over the country, this simplified approach to Mennonite identity constructions proves to be outdated. In order to meet the contemporary challenges, the following thesis proposes to explore Mennonite identities as narrative identities.
Keywords: ddc:420